The Influence of Aging on Pharyngeal Collapsibility During Sleep - Eikermann, Matthias (2007)
BACKGROUND: Aging increases vulnerability to obstructive sleep apnea (OSA), but the underlying mechanisms remain unclear. Recent data in awake healthy volunteers show a decrease in the genioglossus negative pressure reflex and anatomic compromise with increasing age, suggesting an age-related predisposition to pharyngeal collapse. However, aging effects on pharyngeal collapsibility have not been studied extensively during sleep. We tested the hypotheses that upper airway closing pressure (PCLOSE) and the increase in pharyngeal resistance during sleep (primary outcomes) as well as measures of arousal threshold (secondary outcomes) increase with age. METHODS: We studied 21 healthy individuals (8 women [mean (± SD) age, 36 ± 18 years] and 13 men [mean age, 41 ±23 years]) who were between 18 and 75 years of age. During overnight polysomnography, we measured nasal pressure (Pmask) and epiglottic pressure (Pepi) during stage 2 sleep before and after airway occlusion (external valve) until arousal. Pclose was defined as the pressure at which Pmask plateaued despite further decreases in Pepi. RESULTS: Increasing age was correlated with both pharyngeal collapsibility ([Pclose] r = 0.69; p < 0.01) and an increase in pharyngeal resistance during sleep (r = 0.56; p < 0.01) independent of body mass index (BMI) and gender. There was no evidence for an effect of age on arousal threshold after airway occlusion during stage 2 sleep. CONCLUSIONS: Older age is associated with increased pharyngeal airway collapsibility during sleep independent of gender and BMI. These data may at least partially explain the mechanisms underlying the predisposition for pharyngeal collapse in the elderly.